Study protocol, rationale and recruitment in a European multi-centre randomized controlled trial to determine the efficacy and safety of azithromycin maintenance therapy for 6 months in primary ciliary dyskinesia. Issue 1 (December 2016) - Kobbernagel, Helene; Buchvald, Frederik; Haarman, Eric; Casaulta, Carmen; Collins, Samuel; Hogg, Claire; Kuehni, Claudia; Lucas, Jane; Omran, Heymut; Quittner, Alexandra; Werner, Claudius; Nielsen, Kim
Abstract Background Clinical management of primary ciliary dyskinesia (PCD) respiratory disease is currently based on improving mucociliary clearance and controlling respiratory infections, through the administration of antibiotics. Treatment practices in PCD are largely extrapolated from more common chronic respiratory disorders, particularly cystic fibrosis, but no randomized controlled trials (RCT) have ever evaluated efficacy and safety of any pharmacotherapeutics used in the treatment of PCD. Maintenance therapy, with the macrolide antibiotic azithromycin, is currently widely used in chronic respiratory diseases including PCD. In addition to its antibacterial properties, azithromycin is considered to have beneficial anti-inflammatory and anti-quorum-sensing properties. The aim of this study is to determine the efficacy of azithromycin maintenance therapy for 6 months on respiratory exacerbations in PCD. The secondary objectives are to evaluate the efficacy of azithromycin on lung function, ventilation inhomogeneity, hearing impairment, and symptoms (respiratory, sinus, ears and hearing) measured on a PCD-specific health-related quality of life instrument, and to assess the safety of azithromycin maintenance therapy in PCD. Methods The BESTCILIA trial is a European multi-centre, double-blind, randomized, placebo-controlled, parallel group study. The intervention is tablets of azithromycin 250/500 mg according to body weight or placebo administered three times a week for 6 months. Subjects with a confirmed diagnosis of PCD, age 7–50 years, are eligible for inclusion. Chronic pulmonary infections with Gram-negative bacteria or any recent occurrence of non-tuberculous mycobacteria are exclusion criteria. The planned number of subjects to be included is 125. The trial has been approved by the Research Ethics Committees of the participating institutions. Discussion We present a study protocol of an ongoing RCT, evaluating for the first time, the efficacy and safety of a pharmacotherapeutic treatment for patients with PCD. The RCT evaluates azithromycin maintenance therapy, a drug already commonly prescribed in other chronic respiratory disorders. Furthermore, the trial will utilize the Lung clearance index and new, PCD-specific quality of life instruments as outcome measures for PCD. Recruitment is hampered by frequent occurrence ofPseudomonas aeruginosa infection, exacerbations at enrolment, and the patients' perception of disease severity and necessity of additional management and treatment during trial participation. Trial registration EudraCT2013-004664-58 (date of registration: 2014-04-08).